14.6k views
1 vote
Solve for x: -2(x + 3) = -2(x + 1) - 4. (1 point)

a
2.
CA
3
ос
All real numbers
Od
No solution

User Sahira
by
5.1k points

2 Answers

5 votes

Answer:

All real numbers ( -∞ ,∞)

Explanation:

Simplify
-2(x+3)

Apply the distributive property.


-2x-6=-2(x+1)-4

Simplify


-2(x+1)-4


-2x-6=-2x -6

Move all terms containing x to the left side of the equation.

Add 2 x to both sides of the equation.


-2x-6+2x=0

Combine the opposite terms in


-2x-6+2x

add
-2x and
2x


0-6= -6


-6= -6

Since
-6= -6 , the equation will always be true for any value of x . All real numbers

The result can be shown in multiple forms.

All real numbers

Interval Notation:

( − ∞ , ∞ )

User Iskandarblue
by
5.5k points
4 votes

Answer:

no solution

Explanation:


-2 ( x + 3) = -2 (x + 1) -4 \\-2x + 3 = -2x -2 -4\\-2x + 3 = -2x - 6

add
2x to both sides


-2x + 3 + 2x = -2x - 6 + 2x \\3 = -6

That's impossible

so the equation no solution

User Chico
by
5.1k points